Acting and Dancing during the COVID-19 Pandemic as Art Therapy for the Rehabilitation of Children with Behavioural Disorders Living in Socially Disadvantaged Environments - Diana-Lidia; Andrei Tache-Codreanu (MDPI AG, 2024)
Art therapy is employed in numerous ways in rehabilitation. This study focuses on an art and movement therapy project carried out during the COVID-19 pandemic. Acting and dancing methods were adapted to produce a short musical film series for ten children from disadvantaged social backgrounds displaying nonorganic behavioural disorders. The aim was to acquire novel ways of expression on the part of the participants to release painful emotions in a safe setting using the method of catharsis through acting and dancing, triggering relaxation as a physiological response and improving their attitude. This study retrospectively analyses the changes in the children's behaviour and their active participation in the project through quantitative and qualitative research. The children improved their attention and self-esteem, their behaviour became less aggressive and impulsive, and half showed increased empathy. The active participation rate during the project was 82%.